The RAND Online Measure Repository for Evaluating Psychological Health and Traumatic Brain Injury Programs The RAND Toolkit, Volume 2 - Acosta, Joie D. (RAND Corporation, 2014)
This report describes the RAND Online Measure Repository, a tool that contains descriptions of 171 measures of psychological health and traumatic brain injury. Detailed information is provided for each measure in an online searchable database, including measure domains, uses, psychometrics, and costs. This report describes development processes and contains summary information for each measure.